2022
DOI: 10.1002/cam4.5228
|View full text |Cite
|
Sign up to set email alerts
|

A stratified therapeutic model incorporated with studies on regulatory B cells for elderly patients with newly diagnosed multiple myeloma

Abstract: Objective Despite the availability of new agents, elderly patients with multiple myeloma (MM) usually present with poor outcomes due to the heterogeneity of disease conditions, especially immune deficiency. Regulatory B cells (Bregs) can be involved in immune defects by exerting immune regulatory functions in MM. In order to provide more evidence‐based practice for the elderly MM, the study established and assessed a stratified therapeutic model with studies on Bregs for Chinese Elderly Multiple M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Besides, this study revealed a distinct difference in the attrition rates among MM patients of different ages. The attrition rates from 1st LOT through 5th LOT among MM patients ≥65 years old were generally higher than MM patients <65 years old, which may be explained by the different baseline conditions of these two groups of MM patients and elderly MM patients are usually frail and presented with more comorbidities ( Lee et al, 2021 ; Tang et al, 2022 ). The median treatment duration was approximately six to 8 months across all LOTs, similar to other real-world study ( Fonseca et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…Besides, this study revealed a distinct difference in the attrition rates among MM patients of different ages. The attrition rates from 1st LOT through 5th LOT among MM patients ≥65 years old were generally higher than MM patients <65 years old, which may be explained by the different baseline conditions of these two groups of MM patients and elderly MM patients are usually frail and presented with more comorbidities ( Lee et al, 2021 ; Tang et al, 2022 ). The median treatment duration was approximately six to 8 months across all LOTs, similar to other real-world study ( Fonseca et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…Elderly MM patients often have many comorbidities and generally cannot tolerate intensive chemotherapy or ASCT, resulting in a poorer prognosis than younger patients. The optimal treatment regimen for TIE-NDMM is currently unclear (22)(23)(24). The treatment choice must balance efficacy and toxicity to achieve the best possible effectiveness with the least toxic regimen as far as possible.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the population and activation of Bregs are increased at the very beginning stage of MM [ 131 ] and during the transition from MGUS to MM [ 132 ]. It also has been observed that the proportion of Bregs in MM patients is closely correlated with treatment efficacy and prognosis [ 133 , 134 ].…”
Section: Bm Tumor Microenvironment and The Critical Reactions In Mult...mentioning
confidence: 99%